High-frequency scattering by an isorefractive wedge with the parabolic equation method. - Graglia, R.D (IEEE Transactions on antennas and propagation)
The parabolic equation (PE) method is applied to the problem of the high-frequency scattering from a diaphanous wedge, that is, a wedge made of a material which is isorefractive with respect to the surrounding medium, illuminated by a plane wave or by a line current parallel to the edge. The proposed approach is able to handle any wedge aperture and incidence angle and presents some novelties that allows overcoming the problems arising in the numerical solution of the parabolic equation applied to penetrable wedges